Efektivitas Terapi Psikoedukasi terhadap Kemampuan Keluarga dalam Merawat Orang Dengan Gangguan Jiwa (Window of Nursing Journal, 2025)
Family is a very important factor in the healing process of clients who experience mental health problems. One of the therapies that can be given to clients and families is psychoeducational therapy. This study aims to determine the effect of psychoeducational therapy on the ability of families to care for people with mental disorders in the UPTD Working Area of ​​Marusu Health Center Regency Maros. This research is a quantitative research with a pre-experimental design research design with a one group pretest-posttest research design carried out in the UPTD Working Area of ​​Marusu Health Center Kab. Maros in September 2022. The population in this study was 63 people and the sample was taken using a purposive random sampling method in accordance with predetermined criteria with a sample of 35 respondents. The test test in this study used a paired sample t-test with a significance level (ρ < 0.05). The results showed that before psychoeducation therapy was carried out, the family's ability to care for people with mental disorders in the poor category was 35 (100%). After doing psychoeducation therapy, it was found that the ability of families in the poor category was 5 respondents (14.3%) and 30 respondents (85.7%). The results of the paired t-test statistic obtained the value of = 0.000. The conclusion of this study is that there is an effect of psychoeducational therapy on the ability of families to care for people with mental disorders. Therefore, it is recommended to continue to provide support to families who have mental disorders and to conduct regular consultations with health health workers related to family development.